Authentication of Iceland Moss (Cetraria islandica) by UPLC-QToF-MS chemical profiling and DNA barcoding - Xu, Maonian; Heidmarsson, Starri; Thorsteinsdottir, Margret; Kreuzer, Marco; Hawkins, Julie; Omarsdottir, Sesselja; Olafsdottir, Elin Soffia (Food Chemistry, 2018)
The lichen Cetraria islandica or Iceland Moss is commonly consumed as tea, food ingredients (e.g. in soup or bread) and herbal medicines. C. islandica, which has two chemotypes, can be difficult to distinguish from the sister species Cetraria ericetorum. They are collectively referred to as the Cetraria islandica species complex. This study aimed to use an UPLC-QToF-MS chemical profiling together with DNA barcoding to distinguish species and chemotypes of the C. islandica species complex. Our results show that the two chemotypes of C. islandica are clearly distinguishable from each other and from C. ericetorum by the chemometric approach. The RPB2 barcode was able to differentiate C. islandica from C. ericetorum with a barcode gap, but the widely used nrITS barcode failed. Neither of them could discriminate chemotypes of C. islandica. In conclusion, this integrative approach involving chemical profiling and DNA barcoding could be applied for authentication of Iceland Moss materials.